Desiminasi Analisis Instrumen Kabupaten Sehat Sebagai Implementasi Good Govenrnance Di Kabupaten Tana Tidung - Daud Nawir; Nur Indah Noviyanti; Hendy Lesmana; Gusriani Gusriani (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The strategic plan in community development is the obligation of every ministry that refers to the (RPJMN. The Ministry of Health and the Ministry of Home Affairs have agreed on the implementation of a program that accommodates all aspects/orders in realizing a clean, comfortable, safe, and healthy Regency/City to live in as a place to live). improve productivity and regional economy as well as better people's livelihoods. There are 10 categories of healthy districts/cities which are divided based on specific problems, namely: 1) residential areas, public facilities and infrastructure; 2) Independent Healthy Community Life, Food Security and Nutrition; 3) Market; 4) Education; 5) Healthy Social Life and Disaster Management; 6) Transportation and Traffic Regulations; 7) Offices, Industry, IKM and MSMEs; 8) Tourism; 9) Houses of Worship; 10) Smart City/Smart City. The method used in the form of filling out questionnaires, interviews, FGDs, and secondary data. The results of this activity indicate that it is necessary to make better efforts from the government and the community to achieve the Healthy District award. Starting from the ODF prerequisites, the presentation is still quite low, while some key indicators have been met with an estimated percentage of 70%. Mandatory arrangements and additional arrangements are still needed strategies to improve and fulfill indicators/aspects/criteria for healthy district instruments. The benefits of this PKM are as guidelines and evaluation materials for the government in an effort to improve the health and welfare of the community in Tana Tidung Regency